Are we underestimating the full potential of early thrombolytic treatment in patients with acute myocardial infarction?. Issue 5 (1st May 2003) - Terkelsen, C J; Lassen, J F; Nørgaard, B L; Gerdes, J C; Nielsen, T T; Andersen, H R
Abstract : Use of the Boersma curve in order to describe the beneficial effect of thrombolytic treatment at different treatment delays seems questionable, because the curve may underestimate the favourable prognostic effects of early thrombolysis in patients with acute myocardial infarction